Transmisión de Datos de Señal ECG Comprimida Sobre Redes de Datos Urbanas - Aparicio Pico, Lilia Edith; Arco Ríos, Pedro José (Ingeniería, 2001)
This paper shows the third phase of researche about error control transmisión of electrocardiographic signal data compressed with vectorial quantizer, the data has been transmited on CAPITEL data networks.